Immobilization stress sensitizes rat dorsal horn neurons having input from the low back - Hoheisel, Ulrich; Gass, Peter; Mense, Siegfried (European journal of pain, 2015)
Background: Stress is known to promote several forms of muscle pain including non-specific low back pain. However, the question if stress alone activates nociceptive central neurons has not been studied systematically. Here, we investigated the influence of repeated immobilization stress on dorsal horn neurons and behaviour in the rat. Methods: The stress consisted of immobilization in a narrow tube for 1 h on 12 days. Single dorsal horn neurons were recorded with microelectrodes introduced into the spinal segment L2. In this segment, about 14% of the neurons responded to mechanical stimulation of the subcutaneous soft tissues of the low back in naïve rats. The neurons often behaved like wide dynamic range cells in that they had a low mechanical threshold and showed graded responses to noxious stimuli. Results: The stress-induced changes in neuronal response behaviour were (1) appearance of new receptive fields in the deep tissues of the hindlimb, (2) increased input from deep soft tissues, but unchanged input from the skin and (3) significant increase in resting activity. Surprisingly, the pressure-pain threshold of the low back remained unchanged, although dorsal horn neurons were sensitized. In the open field test, the rats showed signs of increased anxiety. Conclusions: This study shows that stress alone is sufficient to sensitize dorsal horn neurons. The data may explain the enhanced pain low back patients report when they are under stress. The increased resting discharge may lead to spontaneous pain.
Gesehen am 22.01.2018